PENGARUH PENDIDIKAN, PENGALAMAN KERJA DAN SIKAP TERHADAP KINERJA GURU DI SMP NEGERI 6 KOTA SUNGAI PENUH - Mauledy Ahmad (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to determine the influence of education, work experience and attitudes on teacher performance at SMP Negeri 6 Sungai Full City partially and simultaneously. The population in this study were all teachers who held positions/classes at SMP Negeri 6 Sungai Full City, namely 30 people. The sampling technique used in this research is saturated sampling. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis tools used are descriptive analysis, multiple regression analysis and coefficient of determination. The results of the research show that there is a significant influence between education on teacher performance at SMP Negeri 6 Sungai Full City, simultaneously there is a significant influence between education, work experience and attitudes towards teacher performance at SMP Negeri 6 Kota Sungai Full, which can be proven. Meanwhile, the magnitude of the influence of education, work experience and attitudes on teacher performance at SMP Negeri 6 Sungai Full is 66.7%. Meanwhile, the remaining 33.3% is explained by other causal factors not examined in this study